Eco-justice Pedagogy All’Italiana: Radical Italian Art in the Italian-language Classroom - Formato, G. (Theory and Practice in Language Studies, 2020)
The climate crisis threatens our very existence in a myriad of urgent ways and thus merits imperative focus in pedagogic practices in general. This focus is achievable in Italian-language classrooms, where issues of global warming and climate crises are seldom mentioned, through artistic themes from Italy’s rich cultural heritage of the arts. The radical art movement of Arte Povera has the potential to bring ecological concerns to the forefront through a critical cultural lens of the country. By drawing upon images of the Arte Povera movement, concepts of eco-justice and eco-pedagogy can occur through paradigms of art-based education to not only discuss the impact of the climate crisis in Italy, but also achieve Italian-language acquisition critically.